PARTISIPASI MASYARAKAT DALAM PEMBANGUNAN DI DESA RAWANG SARI KECAMATAN PANGKALAN LESUNG KABUPATEN PELALAWAN TAHUN 2022 - Sari, Widya Firdia; ,, Adlin (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2025)
This research is motivated by the importance of community participation in the success of village-level development. The objective is to identify the level of community participation in development in Rawang Sari Village, Pangkalan Lesung District, Pelalawan Regency in 2022. This study uses a descriptive mixed methods approach, with data collection techniques including questionnaires, interviews, documentation, and literature review. The theoretical framework used is Cohen and Uphoff's participation model, which divides participation into four main stages: planning, implementation, acceptance, and development evaluation. The results of the study show that the level of community attendance in the Village Development Deliberation in 2022 is still relatively low, namely only 33 people out of 80 invitees (41.25%). However, community participation is present in various forms at each stage of development: At the Planning stage, the most dominant form of participation is in the form of money (24%). At the Implementation stage, the most dominant form of participation is in the form of ideas (26%). At the Acceptance stage, the most dominant form of participation is in the form of expertise. At the Assessment stage, the most dominant form of participation is in the form of ideas. Keywords: Community Participation, Village Development, Planning.